2020
DOI: 10.1093/mnras/staa002
|View full text |Cite
|
Sign up to set email alerts
|

Detecting double neutron stars with LISA

Abstract: We estimate the properties of the double neutron star (DNS) population that will be observable by the planned space-based interferometer LISA. By following the gravitational radiation driven evolution of DNSs generated from rapid population synthesis of massive binary stars, we estimate that around 35 DNSs will accumulate a signalto-noise ratio above 8 over a four-year LISA mission. The observed population mainly comprises Galactic DNSs (94 per cent), but detections in the LMC (5 per cent) and SMC (1 per cent)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 82 publications
(83 citation statements)
references
References 71 publications
2
81
0
Order By: Relevance
“…after 10 years observation with MeerKAT, MeerKAT+ and SKA 1-mid, and 0.5% precision after 15 years. Moreover, LISA is expected to find DNS systems with a characteristic orbital period of 20 minutes in the near future (Lau et al 2020). Such discoveries can significantly tighten the constraints for the EOS.…”
Section: Resultsmentioning
confidence: 87%
“…after 10 years observation with MeerKAT, MeerKAT+ and SKA 1-mid, and 0.5% precision after 15 years. Moreover, LISA is expected to find DNS systems with a characteristic orbital period of 20 minutes in the near future (Lau et al 2020). Such discoveries can significantly tighten the constraints for the EOS.…”
Section: Resultsmentioning
confidence: 87%
“…Lau et al (2020) use a synthesised DNS population to predict that a 4-yr Laser Interferometer Space Antenna (LISA) mission (Amaro-Seoane et al 2017; Baker et al 2019) will detect 35 Galactic DNSs. Andrews et al (2020) predict between 46 and 240 Galactic DNSs for the same mission, depending on the assumed physical assumptions.…”
Section: Discussionmentioning
confidence: 99%
“…However, this extrapolation does not account for differences between the Galaxy and other environments (Abadie et al 2010), and all rate intervals are broad. Lau et al (2020) use a synthesised DNS population to predict that a 4-yr Laser Interferometer Space Antenna (LISA) mission (Amaro-Seoane et al 2017;Baker et al 2019) will detect 35 Galactic DNSs. Andrews et al (2020) predict between 46 and 240 Galactic DNSs for the same mission, depending on the assumed physical assumptions.…”
Section: Dns Merger Ratesmentioning
confidence: 99%
“…As a result, these systems are closer to merger and spend a relatively short amount of time in this subclass of DNS systems compared to the larger orbital period merging DNS systems from Pol et al (2019), which results in an overall smaller population size of ultra-compact DNS systems. The upper limit on the number of ultra-compact DNS systems is also consistent with recent estimates of the size of this population made by Lau et al (2020) and Andrews et al (2020).…”
Section: Size Of Populationsupporting
confidence: 88%
“…These UCB systems can consist of any combination of white dwarf, neutron star or black holes, with the most common source (∼ 10 7 in the Galaxy) being double white dwarf (DWD) binaries (Nelemans et al, 2001a,b). However, population synthesis simulations have shown that LISA should also detect a few tens of ultra-compact double neutron star (DNS) and neutron star-white dwarf (NS-WD) systems (Andrews et al, 2020;Lau et al, 2020). UCB systems are "verification binaries" for LISA, i.e.…”
Section: Introductionmentioning
confidence: 99%